Outcomes of conventional versus virtual surgical planning of orthognathic surgery using surgery-first approach for class III asymmetry - Liao, Yu-Fang; Chen, Ying-An; Chen, Yi-Chieh; Chen, Yu-Ray (Clinical oral investigations, 2020)
Objectives To determine if patient outcome variables differ between conventional and virtual surgical planning of orthognathic surgery for class III asymmetry. Material and methods This retrospective case-control study examined 95 patients with class III asymmetry who had been consecutively treated with at least a Le Fort I osteotomy and a bilateral sagittal split osteotomy with a surgery-first approach. Two groups were examined: 51 patients treated with conventional surgical planning and 44 with virtual surgical planning. After treatment, quantitative assessment was determined with measurements of midline symmetry, contour symmetry, and overall facial symmetry using standardized frontal photographs. Subject assessments were analyzed with questionnaires regarding self-perception of overall appearance, satisfaction with appearance, and quality of life. Results Conventional and virtual surgical planning resulted in significant improvements in outcomes for all patients. However, facial midline and overall facial symmetry were significantly greater for the virtual compared with the conventional group. There were no significant differences in subjective measures of appearance, satisfaction with appearance, and quality of life for patients treated with conventional or virtual surgical planning; measures were high for both groups. Conclusions Conventional and virtual surgical planning of surgery-first bimaxillary orthognathic surgery resulted in quantitative and qualitative improvements in facial symmetry. Although patient satisfaction was similar for both approaches, virtual surgical planning was superior to conventional surgical planning for the improvement of midline and overall asymmetry. Clinical relevance Improvements with virtual surgical planning in facial midline, facial contour, and overall facial symmetry are as good as or better than conventional surgical planning.